BEHAVIORAL INTERVENTIONS IN AGING RESEARCH: CHALLENGES AND OPPORTUNITIES FROM DISCOVERY TO IMPLEMENTATION. (11th November 2018) - Washington, T R; Gitlin, L; Mingo, C
Abstract: Behavioral interventions show promise in mitigating the burden of social and public health issues negatively impacting the health of older adults and their families. However, design and implementation challenges persist. This symposium will highlight challenges and opportunities when designing and implementing behavioral interventions in aging research. The first presentation will highlight recent discoveries in the relationship between obesity and cognition that inform the development of behavioral health interventions with older African Americans. The second presentation will discuss grant writing challenges and provide recommendations for the design of interventions in the early developmental stages using the Music and Sleep feasibility study as an example. The third presentation will share findings from an organizational readiness assessment to implement an evidence-based health promotion intervention in healthcare facilities. The fourth presentation will explore challenges to implementing a peer-led physical activity program in senior centers and methods to build capacity for sustainment. The final presentation will highlight practical challenges in intervention delivery such as staffing, oversight of staff, and fidelity using results from the Michigan Stroke Transitions Trial as a case example.